ANALISIS KARAKTERISTIK PENGGUNA MODA TRANSPORTASI ONLINE DAN TRANSPORTASI KONVENSIONAL DI KOTA DENPASAR (Contoh Kasus: Go-Car dan Sarbagita) - Cartona, Rosnyati; Astati Sukawati, Ni Ketut Sri; Wirasutama, Cokorda Putra (Jurnal Ilmiah Teknik Universitas Mahasaraswati Denpasar (JITUMAS), 2021)
The selection of transportation modes in Denpasar aims to identify the characteristics of users of online transportation modes (Go-Car) and conventional transportation (Sarbagita). Conventional transportation sarbagita also conduct transaction systems without the use of information technology systems, Over time the public considers that the use of transportation must be adjusted to the main needs such as coefficients of time and distance so that the purpose of the use of transportation can support the needs of the community that must be created by the coefficient of time and fares in accordance with the distance traveled such as online transportation modes. The questionnaire in this study in the form of google form was then distributed through online media to respondents and processed using multiple linear regression analysis approach with the help of SPSS V25 program. The results of the study of 100 respondents there were 94 respondents who chose the online transportation mode (Go-Car) and 6 respondents who chose conventional mode of transportation (Sarbagita). From the analysis of data shows that the age of users of online transportation modes (Go-Car) and conventional transportation (Sarbagita) in Denpasar city is 16-55 years, the gender of users of online transportation modes (Go-Car) and conventional transportation (Sarbagita) in Denpasar city is 44% who are men and 56% are women, users of online transportation modes (Go-Car) and conventional transportation (Sarbagita) based on the last level of junior high school as much as 1% , SMA as much as 55%, and S1 as much as 44%, users of online transportation modes of transportation (Go-Car) and conventional transportation (Sarbagita) based on work consists of Students 7%, Students 28%, Private 49%, Self-employed 1%, Housewives 8%, and civil servants 7%.Keywords: Characteristics, SPSS V25, Multiple Linear Regression.